Impact of interannual changes of large scale circulation and hydrography on the spatial distribution of beaked redfish (Sebastes mentella) in the Irminger Sea - Nunez-Riboni, Ismael; Kristinsson, Kristján; Bernreuther, Matthias; Aken, Hendrik Mattheus van; Stransky, Christoph; Cisewski, Boris; Rolskiy, Alexey (Deep Sea Research Part I: Oceanographic Research Papers, 2013)
This study provides evidence of the influence of hydrography and large scale ocean circulation on the geographical distribution of beaked redfish (Sebastes mentella) in the Irminger Sea on the interannual time scale, from 1992 to 2011. The results reveal the average relationship of adult pelagic redfish to their physical habitat from 100 to 800 m depth: the most preferred latitude, longitude, depth, temperature and salinity for redfish are approximately 58°N, 41°W, 557 m, 4.5 °C and 34.87, respectively. The redfish habitat corresponds in a temperature–salinity (TS) diagram to a mixing triangle between East Greenland Current Water (EGCW), Labrador Sea Water (LSW) and Irminger Current Water (ICW). The geographical centre of mass of the redfish distribution (as revealed by acoustic fish density) indicates displacements from year to year. Changes in hydrographic conditions were investigated in detail for possible reasons for these displacements. Empirical Orthogonal Analysis reveals that maximum variations of water mass volume on an interannual time-scale in the study region correspond to ICW and LSW changes, while EGCW remains comparatively stable. Indices of redfish geographical centroid, LSW volume, ICW temperature and Subpolar Gyre (SPG) intensity suggest that the geographical redfish displacements are closely related to interannual changes of ICW modulated by the SPG intensity with a lag of 1 or 2 years. In comparison, LSW seems to have no impact on the redfish distribution at the studied depth range. The time lag between ICW and redfish displacements indicates an indirect influence of temperature on redfish. Hence, changes of chlorophyll-a (from satellite imagery), as a proxy for primary production, were used in a first approach to study the role of food availability. The analysis is based on acoustic and trawl data from nine expeditions coordinated by the International Council for the Exploration of the Sea (ICES), around 71,000 hydrographic stations from the Integrated Climate Data Center, World Ocean ...